Effect of colorant, film thickness, and pro-oxidant loading on the impact of degrading oxo-biodegradable low-density polyethylene films to water quality - Requejo, Benedict A.
Polyethylene (PE) is a major component to plastic wastes disposed in bodies of water because of its widespread use. To address its low degradability, PE blended with metal pro-oxidants (oxo-biodegradable PE), which under the presence of UV, heat, and oxygen degrade much faster, has been developed. However, pollutants from oxo biodegradable PE have a greater tendency to be released onto bodies of water. In this study, oxo-biodegradable PE films were immersed in deionized water at 50 degree celsius for 1176 h. Water quality was investigated by monitoring pH, oxidation-reduction potential (ORP), electrical conductivity (EC), total dissolved solids (TDS), and turbidity at regular intervals. Components used to formulate the oxo-biodegradable PE were analyzed through energy dispersive X-ray fluorescence spectroscopy (EDX) to identify presence of toxic metals. Oxo-biodegradable PE films that were found to contain these were immersed in deionized water at 70 degree celsius for 840 h, and leachate concentration was monitored through microwave plasma atomic emission spectroscopy (MP-AES). It was observed that pH initially rises and then slowly decreases with time, ORP initially decreases then slowly increases with time, EC and TDS generally increases with time, and turbidity rises above the control but fluctuates. Main effects of factors were also compared at 1176 h and select time intervals. Yellow colorant was revealed to contain lead and chromium, which leach out from the yellow films over time.